Longitudinal Examination of Everyday Executive Functioning in Children With ASD: Relations With Social, Emotional, and Behavioral Functioning Over Time - Vogan, Vanessa M.; Leung, Rachel C.; Safar, Kristina; Martinussen, Rhonda; Smith, Mary Lou; Taylor, Margot J. (Frontiers in Psychology, 2018)
Executive functioning (EF) deficits are well-documented in Autism Spectrum Disorder (ASD), yet little is known about the longitudinal trajectory of ‘everyday’ EF and links to social, emotional and behavioural outcomes in ASD. This study examined the profile of everyday EF utilizing parent-reported measures over 2 years, and explored whether prior estimates of EF were related to later co-morbid psychopathology and social functioning in 39 children with ASD and 34 typically developing (TD) children (ages 7-14 years). According to parent reports, children with ASD had impaired scores of EF in all domains at both time points, and showed no significant improvement across 2 years, compared to controls. Regression analyses showed that prior estimates of behaviour regulation difficulties at time 1 uniquely predicted later emotional (i.e., symptoms of anxiety/depression) and behavioural (i.e., oppositionality/aggressiveness) problems in children with ASD 2 years later. Furthermore, an improvement of metacognitive skills predicted a reduction of social difficulties over 2 years in ASD. These results imply that EF may be a potential target of intervention for preventing and reducing co-morbid psychopathology and promoting social competence in youth with ASD. Furthermore, the findings that EF related to behaviour is more critical for later emotional and behavioural functioning, whereas EF related to cognition is more critical for social functioning, indicates that it may be beneficial to tailor treatment. Future studies investigating the effectiveness of EF-based interventions in improving the cognitive, psychological and social outcomes in ASD are of high priority.